Of tradition and creation: the discourse of fashion designers on trend report usage - Campos, Amanda Queiroz (2017)
Tese (doutorado) - Universidade Federal de Santa Catarina, Centro de Comunicação e Expressão, Programa de Pós-Graduação em Design, Florianópolis, 2017.